2014
DOI: 10.1016/j.psychres.2014.08.060
|View full text |Cite
|
Sign up to set email alerts
|

The MATRICS Consensus Cognitive Battery (MCCB): Performance and functional correlates

Abstract: Neurocognitive impairment is a core feature in psychotic disorders and the MATRICS Consensus Cognitive Battery (MCCB) is now widely used to assess neurocognition in this group. The MATRICS has been translated into several languages, including Norwegian; although this version has yet to be investigated in an adult clinical population. Further, the relationship between the MATRICS and different measures of functioning needs examination. The purpose of this study was to describe neurocognition assessed with the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
4
15
0
Order By: Relevance
“…More recently, a meta-analysis study revealed that a variety of neurocognitive domains such as reasoning and problem solving, processing speed, attention and vigilance, working memory, verbal learning and memory, visual learning and memory, verbal fluency, and overall neurocognition are significantly associated with functional outcome 39. Lystad et al reported that among the MCCB cognitive domains, working memory was the most highly correlated with months of previous employment and social function evaluated by the SFS and was a significant predictor of social function 48. Torgalsbøen et al showed that MCCB attention/vigilance was a significant predictor of social and role functioning assessed by Global Functioning 52.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a meta-analysis study revealed that a variety of neurocognitive domains such as reasoning and problem solving, processing speed, attention and vigilance, working memory, verbal learning and memory, visual learning and memory, verbal fluency, and overall neurocognition are significantly associated with functional outcome 39. Lystad et al reported that among the MCCB cognitive domains, working memory was the most highly correlated with months of previous employment and social function evaluated by the SFS and was a significant predictor of social function 48. Torgalsbøen et al showed that MCCB attention/vigilance was a significant predictor of social and role functioning assessed by Global Functioning 52.…”
Section: Discussionmentioning
confidence: 99%
“…The demographic and clinical characteristics of the participants are presented in Table . The recruitment process and test procedure of the participants in the schizophrenia group have been described elsewhere . Briefly, this sample consisted of 131 participants (92 men, 39 women) aged 18–65 years in a multisite vocational rehabilitation study (the Job Management Program [JUMP]) for adults with a main diagnosis of psychotic disorders, meeting the criteria according to the DSM‐IV .…”
Section: Methodsmentioning
confidence: 99%
“…The CPT-IP score was omitted when calculating the MCCB total score to avoid biasing predictive relationships. The MCCB neurocognitive composite score was calculated using the mean of the domain T -scores, as is consistent with prior publications 30 . The 5C-CPT was completed following the diagnostic and cognitive assessments.…”
Section: Methodsmentioning
confidence: 95%